Health and Medicine in the Islamic Tradition Based on the Book of Medicine (Kitab al-Tibb) by Sahih al-Bukhari - Alidjanova Lazizkhon Abbasovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article studied the book on medicine (Kitab al-Tibb) in Sahih al-Bukhari. The book of medicine is in book 76, which consists of 58 chapters with 105 hadiths. The titles of each chapter in the book of medicine reflect the content of the hadeeth which relates to the medical matter and what comes out of it. The Book of Medicine (Kitab al-Tibb) gives first of all an idea of ​​the state of the Muslims in the time of the Prophet (pbuh), how they prevented and cured diseases. It turns out that most of al-tibb an-nabawi relates to preventive medicine (al-tibb al-wikai), and not to therapeutic (al-tibb al-ilaji), and was practiced at the time of the Prophet (pbuh) and after him.